A rare cause of bile duct obstruction in adolescence: Neuroendocrine tumor - Yalav, Orçun; Ülkü, Abdullah; Demiryürek, Haluk; Doran, Figen (Turkish Journal of Gastroenterology, 2014)
Abstract Extrahepatic bile duct is one of the rare places for neuroendocrine tumors which comprise 0.2-2 % off all neuroendocrine tumors of gastrointestinal tract. The aim of this paper is to report a case of a 16-year-old boy with a neuroendocrine tumor of extra hepatic bile duct. Laboratory and imaging findings is supported obstructive jaundice. After a pre-operative detailed evaluation, the common bile and common hepatic duct with gallbladder were resected and Roux-en-Y hepaticojejunostomy was performed. After a 36 months follow up, no locoregional recurrence or metastatic disease was observed. Pre-operative diagnosis of neuroendocrine tumors are extremely difficult and often confused with cholangiocarcinoma. Treatment modality of this rare entity depends on the location of the tumor and aggressive surgery is still the best chocie of treatment. It should be kept in mind that disease-free survival for patients with neuroendocrine tumor depends on success of surgery.